26. PALYNOLOGICAL AND GEOCHRONOLOGICAL STUDY OF THE HOLSTEINIAN/HOXNIAN/LANDOS INTERGLACIAL - A.Geyh M.; Müller H. (My University, 2007)
The discovery of a pollen assemblage in interglacial deposits comparable with that of the pollen assemblage zone (PAZ) MM 8 of the Holsteinian Interglacial at Munster Breloh allows us to distinguish coeval deposits from those of other pre-Eemian interglacials. Thus, there is palynological evidence for a reliable correlation of precisely investigated and numerically dated Holsteinian deposits with the Mazovian Interglacial (eastern Poland), the Hoxnian Interglacial (England and SW Ireland) as well as the Landos Interglacial in the Massif Central (France). Adapting the palynological correlation of the Praclaux Interglacial, Massif Central, with MIS 11, the Holsteinian/ Hoxnian/ Mazonian/ Landos interglacial belongs to MIS 9. 230Th/U dates from fen peat layers of the Holsteinian reference site at Bossel in northern Germany and from two sites with Hoxnian deposits in England date these interglacial deposits to about 320 kyr BP corresponding to MIS 9. This correlation is supported by supplementary 230Th/U dates of fen peat from several both pre-Eemian and non-Holsteinian sites in Germany. © 2007 Elsevier B.V. All rights reserved.